ANALISIS DETERMINAN ELEMEN FRAUD TRIANGLE TERHADAP KECURANGAN LAPORAN KEUANGAN DENGAN BENEISH M-SCORE MODEL PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2022 - Mustakim, Ridho Dewo; Kurniawati, Lintang (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
Using the fraud triangle concept, this study aims to provide empirical evidence on the variables influencing financial statement fraud. The fraud triangle identifies three factors contributing to fraudulent financial reporting: pressure, opportunity, and rationalization. This research employs a quantitative method using secondary data from the financial statements of state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange during the 2020-2022 period. The purposive sampling method was applied, resulting in a final sample of 48 data points. Hypotheses were tested using panel data multiple linear regression analysis. The results indicate that pressure, proxied by financial stability, has a positive effect, while external pressure has a negative effect on financial statement fraud. However, pressure proxied by financial targets, opportunity proxied by ineffective monitoring, and rationalization proxied by auditor changes do not significantly influence fraudulent financial reporting.